The acute effect of two resistance-training intensities on flow-mediated dilation in physically-active young males - Briceño Torres, José Miguel (2016)
Purpose: The purpose of the study was to determine the acute effect of two resistance-training exercise intensities on flow-mediated dilation (FMD) in physically active Costa Rican males. Methods: Nine males participated in the experimental trial. Participants mean (± SD) age, body height, body weight, and body mass index were 24.4 ± 2.1 yr., 176.1 ± 5.3 cm, 71.9 ± 8.3 kg, and 23.2 ± 2.1 kg/m2, respectively. A physician assessed cardiovascular and health risk factors before participants were allowed to participate in the study. Males reported to the laboratory in the morning after a 12-h rest in three different occasions. Two-elbow flexion exercises at 55% of one-maximum repetition (1-RM) and 80% of 1-RM, as well as a control (no exercise) condition were randomly assigned to each participant. Artery endothelial function was assessed using brachial artery FMD determined by ultrasound before and after three sets of six repetitions with 90-s rest between sets of an elbow flexion exercise, and during supine rest in the control condition. Results: A significant increase was found in end-diastolic flow 30-s following exercise between 80% 1-RM trial (M = 24.0 ± 10.2 cm/s), the 55% 1-RM trial (M = 4.7 ± 9.3 cm/s; p = 0.004) and the control condition (M = 10.9 ± 11.9 cm/s; p = 0.002). Significant increases were found in blood-flow between the 80% 1-RM trial (M = 148.8 ± 60.8 ml/min) immediately following exercise up to 60-s following exercise from the 55% 1-RM trial (M = 68.3 ± 32.3 ml/min; p < 0.021) and the control condition (M = 80.4 ± 54.5 ml/min; p < 0.024). Significant increases were found in end-diastolic flow velocity between the 80% 1-RM trial (M = 41.9 ± 10.4 cm/s) immediately following exercise up to 60-s following exercise from the 55% 1-RM trial (M = 26.9 ± 10.4 cm/s; p < 0.022) and the control condition (M = 32.0 ± 12.9 cm/s; p < 0.043). Conclusions: An acute resistance training protocol at 80% 1-RM improves vascular endothelial response compared to training at 55% 1-RM or the condition control in young males.